The pastor’s ‘love offering’: prosperity gospel and a child witchcraft accusation narrative - Ayelotan, Claire P. (Practical Theology, 2023)
This reflective first-person narrative study emerged from a personal encounter in a village near Eket City in Nigeria. This article adopts a multidisciplinary approach with a theological concentration to understand the issues of beliefs, uncertainty, religious leaders, and prosperity gospels and how these factors contribute to witchcraft labelling. This study brings an untold story to the forefront, using moral narrative techniques. The encounter provoked two lines of reflection. First, it questions the role of Pentecostal leaders: are they rescuers or complicit parties in witchcraft accusations? Second, it examines the ethical implications of these leaders accepting gifts in contexts where poverty is pervasive. The notion of ‘the love offering’ poses ethical questions as it relates to congregants presenting gifts to their clergy, frequently side-lining their moral obligations. As delineated in this study, this dynamic provokes critical inquiry: Are these gifts genuinely acts of love, or are they made in anticipation of a reciprocal benefit from the pastor? Readers are left to draw their own conclusions as they engage with this narrative article.
paid
Keywords: Child witchcraft accusation; Nigeria; Pentecostalism; deliverance; misplaced priority; prosperity theology